Pengembangan Bahan Ajar Digital Berbasis Articulate Storyline pada Pembelajaran Teks Prosedur di Sekolah Menengah Atas - Fatimah, Masni; Burhanudin, Dudung; Permatasari, Silvia (TRANSFORMATIKA, 2024)
Short learning hours mean that learning cannot be carried out effectively. Learning materials that cannot be conveyed well will affect students' understanding, so they require teaching materials that students can study independently and can be accessed at any time. Teaching materials are generally used as learning tools that contain learning materials for a teacher to use in delivering learning. This research aims to develop articulate storyline-based digital teaching materials in the form of learning applications on procedural text material as an alternative for solving existing problems in class 11 Science 1 SMA Muhammadiyah 1 Pekanbaru. The method used in this research is RD through the ADDIE approach. This research uses a Pre-Experimental Design, namely using only one experimental class without a control class with a One-Group Pretest-Posttest Design model. The research instruments used were questionnaires and pre-test and post-test essay questions. The result is that the average percentage of expert validation of products is 92% in the very good category, the average percentage of teacher assessments is 93% in the very good category, the average percentage of student assessments is 90% in the very good category. The research results can be concluded that there are differences in student learning outcomes between learning procedural texts without digital teaching materials in the form of learning applications using digital teaching materials based in the form of learning applications based on the Wilcoxon test of pretest and posttest data with Asymp values. Sig. (2-tailed) of 0.000 0.05